Punishment Under Special Minimum Criminal Threat In the Crime of Child Abuse (Study of Decision Number 1041 K/Pid.Sus/2020) - Rosman Ahmad; Hariman Satria; Faisal Abdaud; Mafardin Mafardin (Faculty of Law, Universitas Pekalongan, 2023)
The imposition of a penalty below the special minimum in the crime of molestation of children is a very important issue in criminal law. This crime aims to provide more effective protection to victims of immorality involving children. In some cases of child abuse, the judge handed down a verdict below the special minimum. The offense that is the focus of this study is how the judge considers sentencing under the special minimum criminal threat based on Decision Number 1041 K/Pid.Sus/2020 in the case of criminal acts of child abuse? The research method used is a type of normative legal research using 2 (two) legal approaches, namely the legislative approach and the case approach. The results of the study concluded that the Supreme Court in decision Number 1041/Pid.sus/2020 has strengthened the judex facti decision that imposes a penalty below the special minimum limit to the defendant so that the decision contradicts the provisions of Article 82 paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection is the minimum limit of 5 (five) years and a maximum of 15 (fifteen) years.